" الهوية "مقاربات مفاهيمية - عماري, فرحات (University of eloued جامعة الوادي, 2018)
تهدف هذه المداخلة إلى تتبع سيرورة مفهوم الهوية بمقاربة أركيولوجية جينيالوجية تستقصي المنازع الكبرى التي تشكل فيها المفهوم وتموضعاته المختلفة، بداية من الفضاء الغربي وكيف رسمت الهوية مسارها من اللحظة السقراطية إلى غاية العصر المعاصر واقتحامها ميدان علوم الانسان، ثم تتبعها مقاربات مجموعة من الأكادميين العرب لموضوع الهوية وكيف شكلت هاجسا للإنسان العربي في ظل التحديات المعاصرة ختاما بطرح الموضوع بنوع من الاستشكال الفلسفي الذي يجد نفسه على ساحة الاشتغال الفكري والمعرفي اليوم The aim of this intervention is to trace the process of the concept of identity to the approach of a genealogical ideology that explores the great conflict in which the concept and its different positions form, beginning with the western space, and how the identity draws its path from the Socratic moment to the contemporary era and its penetration into the field of human sciences, and then follows the approaches of a group of Arab academics to the subject of identity And how it was an obsession for the Arab man in the face of contemporary challenges, concluding with the subject of a kind of philosophical question, which finds itself in the arena of intellectual activity and knowledge today
الملتقى الوطني حول إشكالية الهوية بين التاويل الإيديولوجي والفهم العقلاني -جامعة الشهيد حمه لخضر الوادي-
Keywords: الهوية، المفهوم، الذات، الهوية الثقافية; :Identity, Concept, Self, Cultural identity